PROPHYLAXIS OF «ATYPICAL PNEUMONIA» AT TOMSKAYA PROVINCE - N. S. Zinchenko; E. N. Topovskaya; I. I. Novokshonov (Acta Biomedica Scientifica, 2020)
Materials of the organizing and methodical activities performed by the specialists of State Surveillance Center at Tomskaya Province, Public Health Department, Departmental Services with the support of the Province administration to prevent importation and dissemination of «atypical pneumonia» are represented.